Inverse Correlation between Combination of Antiretroviral Therapy with the level of Serum Interleukin-6, Ferritin, and Hepcidin in HIV Patients with Anemia Chronic Disease - I Ketut Agus Somia; Ketut Tuti Parwati Merati; I Made Bakta; Ida Bagus Putra Manuaba; Wayan Putu Sutirta Yasa; I Dewa Made Sukrama; Ketut Suryana; Rudi Wisaksana (Journal of Global Pharma Technology, 2017)
Background: The purpose of this study was to determine whether the cARV therapy correlates with the serum level of IL-6, ferritin, and hepcidin in HIV infected patients with ACD.Methods: A cross-sectional study conducted in HIV patients with ACD, aged 15-65 years with exclusion criteria such as chronic renal disease, chronic liver disease, treated for anemia in the last 3 months, taking iron supplements in the last 3 months, history of blood transfusion in the last 1 year, suffering from acute infection, tuberculosis infection, malignancy, hepatitis C virus infection, acute hypersensitivity reaction and pregnancy. Blood specimen examined by high sensitivity human IL-6 In vitro ELISA, DRG Hepcidin- 25 ELISA, serum ferritin by agglutination method and CD4 cell count by flow cytometry. Results: A total of 86 HIV patients with ACD consist of 42 subjects with experienced cARV and 44 subjects with naive cARV. There are several differences between cARV naïve and experienced cARV including: Hb (g/dl) [ 10.8 ( 9.88 – 11.75) Vs. 11.60 (11.00 – 12.34) p: 0.058 ], serum iron (mg/dl) [ 50.00 (31 – 66.8) Vs. 71.40 (56.00 – 108.00) p: 0.121 ), serum ferritin (ug/dl) [ 630 ( 194 – 1101) Vs. 195.40 (128.25 – 589.47) p: 0.008 ], IL-6 (pg/mL) [7.20 (3.88 – 10.76) Vs. 4.03 (1.69 – 8.49) p: 0.009), serum hepcidin (ng/mL) [45.54 (16.74 – 95.31) Vs. 23.35 (6.58 – 49.99) p: 0.007] , CD4 cell count (cell/uL) [31.5 (14.25 – 90.75) Vs. 307 (168.5 – 458.75) p : < 0.001)] There is a significant inverse correlation between the cARV therapy with level of serum IL-6 ( r: - 0. 285, p: 0.008), ferritin (r: - 0.321, p: 0.007) and hepcidin (r: - 0.293, p: 0.006). While there was a significant positive correlation between the cARV therapy with CD4 cell count (r: 0.676, p: 0.001). There was no correlation between the cARV therapy with serum iron levels ( r: 0.176, p: 0.121).Conclusion: There is an inverse correlation between the cARV therapy with serum level of IL-6, ferritin, and hepcidin in HIV patients with ACD. Keywords: cARV, ACD, IL-6, Ferritin, Hepcidin.